A critical review on the advances in thermal reduction technology for recycling spent lithium-ion batteries - Jiahao Li; Sabereh Nazari; Xiaoxue Ma; Neng Wei; Yaqun He (Next Materials)
As the new energy vehicle industry expands, the rising volume of decommissioned lithium-ion batteries (LIBs) poses significant challenges related to resource depletion and environmental pollution. To address these issues and promote sustainable recycling practices, researchers have explored various techniques, including pyrometallurgy, hydrometallurgy, and bio-leaching methods. Cathode materials, which account for 26 % of battery costs, are a key focus due to their economic value. This review summarizes thermal reduction recovery technologies for cathode materials in spent LIBs, examining processes such as thermite reduction, carbothermic reduction, and salinization roasting, and evaluating their efficiencies and environmental impacts. The review emphasizes the importance of policy support and technological advancements in advancing the battery recycling sector. It also explores future research directions, including reducing agents derived from spent batteries and assessing the industrial scalability of recycling technologies. In conclusion, this paper provides a comprehensive overview of thermal reduction recovery for spent LIBs, aiming to guide and inspire future research and development.